Report of a Case of a Giant Dumb-Bell Shaped Bartholin's Gland Cyst and Systematic Review of the Literature - Fortunato Genovese; Stefano Siringo; Elisa Leonardi; Attilio Tuscano; Ferdinando A. Gulino; Francesco Cannone; Marco A. Palumbo; Francesco Catania; Stella Capriglione; Francesco G. Martire (IMR Press, 2022)
Background: Bartholin's gland cysts are one of the most frequent masses involving vulva. They may start as cysts without symptoms but if untreated, they may grow, leading to infection and consequent surgical treatment. Up to noe the giant and dumb-bell shaped presentation of Bartholin's gland cyst is reported once in literature. Methods: We performed an online systematic literature review, using PubMed and Medline search to identify all listed publications around giant dumb-bell shaped Bartholin's gland cyst larger than 10 cm. We identified a total of 3 cases. Of these 3 cases, 2 cases were giant Bartholin's duct cyst and only 1 case a giant and dumb-bell shaped Bartholin cyst. We analyzed the diagnosis and the treatment of these 3 cases. Thus, we described our case of a giant and dumb-bell shaped Bartholin cyst and its treatment performed at the Department of Obstetrics and Gynecology of San Marco Hospital in Catania Sicily. After that, we first summarized the large Bartholin's gland cyst hitherto reported and next we summarized the current knowledge of clinical handling of Bartholin's gland cyst in general. Results: Apart from clinical examination, perineal ultrasound was very useful in diagnosis, because of providing more information concerning the dimensions, shape and extent of the cyst. The case presented with two large swellings with a main mass superiorly and a smaller one inferiorly and perineal ultrasound allowed us to realize that the two masses of the cyst were connected each other through a narrow neck. The ultrasound scan was useful also during the marsupialization of the cyst. Conclusions: In the current literature this type of giant and dumb-bell shaped presentation of Bartholin's gland cyst is uncommon and has reported just one time. In addition we highlitght the utility of perineal ultrasound in the management of Bartholin's gland cyst in order to define a right differential diagnosis between cystic and solid vulvar masses.